Magnitude of Anemia and Its Associated Factors Among Pregnant Women Attending Antenatal Care in Hiwot Fana Specialized University Hospital in Eastern Ethiopia - Balis, Bikila; Dessie, Yadeta; Debella, Adera; Alemu, Addisu; Tamiru, Dawit; Negash, Belay; Bekele, Habtamu; Getachew, Tamirat; Eyeberu, Addis; Mesfin, Sinetibeb; Eshetu, Bajrond; Merga, Bedasa Taye; et al. (Frontiers in Public Health, 2022)
Abstract Background: Anemia is a significant public health issue, accounting for 20-40% of maternal deaths. Despite the government's commitment and the interventions of various stakeholders, the magnitude and major risk factors of anemia remain unabated. As a result, the purpose of this study was to determine the magnitude of anemia and associated factors among pregnant women attending antenatal care in university hospital in Eastern Ethiopia. Methods: A facility-based cross-sectional study was conducted on a sample of 456 clients attending antenatal care in Hiwot Fana specialized university hospital from June 01 to 30, 2021. Systematic sampling was used to select the study participants. A pretested and structured interviewer-administered questionnaire and sample collection were used to collect the data. The data were coded, double entered to Epi data version 3.1, cleaned and exported to SPSS version 20 for analysis. Variables with P value <0.25 during bivariate analysis were entered into the multiple logistic regression models to control for all possible confounders to identify factors associated with magnitude of anemia. Odds ratio along with 95% CI were estimated to measure the strength of the association. Level of statistical significance was declared at a p-value less than 0.05. Result: A total of 456 participants were interviewed, with a response rate of 442 (96.9%). The magnitude of anemia among pregnant women was 112(25.3%) 95%CI: (21.5%-29.2%)]. Of which; 27(6.10%), 36(8.13%) and 49(11.08%) had mild, moderate and severe anemia respectively. Birth interval < 2 years [AOR: 3.24, (95% CI: (1.88, 4.32)], number of children ≥2 [AOR: 2.54, (95% CI: (1.12, 4.64)], monthly income < 1000 birr [AOR: 2.89, (95% CI: (1.31, 5.58)], third trimester pregnancy [AOR: 2.89, (95% CI: 4.86, 12.62)] and abnormal menstrual history [AOR: 2.28, (95% CI: (1.69, 5.24)] were factors significantly associated with anemia. Conclusion: About one in fourth pregnant women were anemic and anemia was a moderate public health problem in the study area. Birth intervals, number of children, history of menstrual disorder, monthly income and trimester of pregnancy were all significantly associated with anemia in pregnant women. Keywords: Anemia, Magnitude, pregnant women, Associated Factors, Ethiopia